Law is a moral practice - Hershovitz, Scott (Massachusetts Harvard University Press, 2023)
What is law, and why does it matter? Scott Hershovitz says that law is a moral practice-a tool for adjusting our moral relations. This claim is simple on its face, but it has stark implications for the rule of law. At once erudite and entertaining, Hershovitz's argument engages with the most important legal and political controversies of our time.
A moral practice-- A tale of two textualists-- Not a set of norms-- An immoral practice-- Stop! in the name of law-- Roy Moore and the rule of law-- Lawyers and morality.
Includes bibliographical references and index.
Keywords: Law and ethics; Law -- Interpretation and construction; Law -- Moral and ethical aspects